Cloud RAN and MEC: A Perfect Pairing - Reznik, Alex; Murillo, Luis Miguel Contreras; Fontes, Francisco; Turyagyenda, Charles; Wehner, Christof; Zheng, Zhou (ETSI MEC, 2018)
CRAN and MEC are highly complementary technologies. Collocating these helps make the economics of each of them significantly more attractive. Collocating CRAN and MEC also helps an MNO to support (and generate revenue from) some of the key 5G applications that it would not be able to support otherwise. However, to realize these advantages, mobile operators have to overcome challenges associated with co location, as well as maximize the return that can be made from MEC. We identify and discuss challenges in the management, security, networking and regulatory domains. We argue that these issues are surmountable and the industry is well-positioned to deploy this potentially revolutionary new technology. Moreover collocation can also enable MEC services (e.g. the ETSI defined Radio Network Information API, Location API, UE Identity API and Bandwidth Management API) to exploit CRAN and enable MEC applications to exploit CRAN information. Mobile operators could, for example, resolve the management complexities associated with multiple IaaS stacks, while monetizing services like RNIS, which are unique to MEC edge clouds.
Keywords: Cloud RAN and MEC; Pairing